The Differences of Adaptive and Maladaptive Coping Mechanisms on the Intensity of Maternal Pain in the First Stage of Labor - Khoirun Nisa, Shofia Maharani; Agustina, Wiwik (Faculty of Medicine, UIN Syarif Hidayatullah Jakarta, 2024)
Coping mechanisms are strategies that a person uses when facing feelings that make him uncomfortable, such as stress and anxiety. One of the impacts of stress and anxiety can be increased labor pain. The level of coping mechanisms is thought to describe maternal stress and anxiety so that it can be used as a predictor of labor pain. The aim of this study was to determine the differences in the level of coping mechanisms and the intensity of pain in mothers during the first stage of labor. This study used an analytical observational method with a cross-sectional design. Sampling was carried out using purposive sampling. A total of 66 mothers giving birth at PKU Muhammadiyah Delanggu Hospital were included in this research. The results of the Wilcoxon test show that there are differences in adaptive and maladaptive coping mechanisms for first stage labor pain with a p value <0.005 (CI = 95%). The conclusion of this research is that there are differences between adaptive and maladaptive coping mechanisms for first stage labor pain at PKU Muhammadiyah Delanggu Hospital in the period 15 November 2017 to 23 January 2018.